Molecular and Phylogenetic Analysis of Bovine Papillomavirus Type 1: First Report in Iraqi Cattle - Mohammed A. Hamad; Ahmed M. Al-Shammari; Shoni M. Odisho; Nahi Y. Yaseen (Advances in Virology)
This study aimed to provide the first molecular characterization of bovine papillomavirus type 1 (BPV-1) in Iraq. BPV is a widely spread oncogenic virus in Iraqi cattle and is associated with the formation of both benign and malignant lesions, resulting in notable economic losses in dairy and beef cattle. In the current study, 140 cutaneous papilloma specimens were collected from cattle in central Iraq. These samples were submitted to histopathological examination, PCR, and sequencing analysis. The histopathology revealed that the main lesion type among the specimens was fibropapilloma. BPV-1 DNA was detected in 121 of the samples (86.42%) in Iraqi cattle as the main causative agent for the disease. A partial sequence for the E2, L2 genes, and complete sequence for the E5 gene were deposited in GenBank. Phylogenetic analysis confirmed the presence of BPV-1 and showed that the origin of infection may be imported European cattle. Obtaining a complete E5 gene sequence enabled us to perform structural predictions. This study presents the first report of BPV-1 infection in the Iraqi cattle and contributes to extending the knowledge of the origin of the spread of this disease. The results of this study will aid in the development of appropriate control measures and therapeutic strategies.